MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN MENGANALISIS TEKS BERITA SISWA KELAS VII SMPN 8 MEDAN - Ariesta, Dea; Yuhdi, Achmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the guided inquiry learning model on students’ ability to analyze news texts in the seventh grade at SMPN 8 Medan. This research employed a quantitative method with a pre-experimental design in the form of a one-group pretest-posttest design. The sample of this study consisted of one class, namely class VII-3, with a total of 32 students. The data collection technique used was a test in the form of 25 multiple-choice questions administered during the pre-test and post-test. The data were analyzed using statistical tests to examine the differences in learning outcomes before and after the treatment. The results showed that students' initial ability to analyze news texts before the implementation of the guided inquiry learning model was categorized as low, with an average score of 38.38. After the implementation of the guided inquiry learning model, students' ability increased, with an average post-test score of 82.13, categorized as good to very good. The results of the hypothesis test indicated that there was a significant effect of the implementation of the guided inquiry learning model on students' ability to analyze news texts, as evidenced by a significance value of 0.001<0.05. Therefore, it can be concluded that the guided inquiry learning model has a positive effect on the ability to analyze news texts of seventh grade students at SMPN 8 Medan.